2008
DOI: 10.1086/592969
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Diagnosis of Human Rabies Based on Analysis of Skin Biopsy Specimens

Abstract: Skin biopsy specimens should be systematically collected in cases of encephalitis of unknown origin. These samples should be tested by RT-hnPCR immediately to confirm rabies; if the technique is not readily available locally, the samples should be tested retrospectively for epidemiological purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
144
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(156 citation statements)
references
References 35 publications
5
144
2
5
Order By: Relevance
“…Intermittent shedding of the virus in saliva influences the diagnostic yield. The collection of 3 serial daily saliva samples enhanced the sensitivity to 100 % [116]. The difference in sensitivities between saliva swab samples (52.9 %; 17 samples) and liquid saliva samples (74.6 %; 67 samples) was not found to be statistically significant.…”
Section: Salivamentioning
confidence: 87%
See 4 more Smart Citations
“…Intermittent shedding of the virus in saliva influences the diagnostic yield. The collection of 3 serial daily saliva samples enhanced the sensitivity to 100 % [116]. The difference in sensitivities between saliva swab samples (52.9 %; 17 samples) and liquid saliva samples (74.6 %; 67 samples) was not found to be statistically significant.…”
Section: Salivamentioning
confidence: 87%
“…A recent study demonstrated 100 % specificity in RT heminested PCR targeting the L polymerase gene in antemortem human rabies diagnosis [116]. The study demonstrated higher sensitivity of detection from skin biopsies (98.3 %) than from saliva (70.2 %), irrespective of the time of collection (from day 1 of illness to postmortem), but when 3 daily serial samples of saliva were tested, the sensitivity reached 100 %.…”
Section: Diagnosismentioning
confidence: 95%
See 3 more Smart Citations